Steinbeck Family Portrait - unknown:::Creator::::::::::::
John Steinbeck and his family on the porch of John Adolph Steinbeck. Inscription on back reads: '..Golden wedding anniversary celebration of John Adolph and Almeira Ann Dickson. Top, left to right: Harvey Eugene Steinbeck, Grace Steinbeck, John Adolph Steinbeck, Almira Ann Steinbeck, Charles Earl Steinbeck. Third row, left to right: Elizabeth Steinbeck Will Steinbeck, Karl Steinbeck, Richard Steinbeck, Fred Steinbeck, Niva Steinbeck. (John and his family identified below--other identifications incomplete) John Steinbeck center front; John Ernst (father) 2nd from left, [sitting]; Mary (sister) on his lap; Olive (mother); Elizabeth standing above mother. Esther, 3rd to the right of mother.'